2020
DOI: 10.1109/access.2019.2962311
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Internal and External Funding Mechanisms Considering Green Consumer Loyalty: A Game-Theoretic Approach

Abstract: Since financing issues of research and development (R&D) directly determine the success of green supply chain initiatives, the choice of funding mechanisms becomes key for green supply chain participants. However, there are few quantitative studies on the financing issues of green supply chains. We study green R&D financing issues for a two-echelon green supply chain, in which a green manufacturer and a regular manufacturer produce and sell green and regular products to a retailer, respectively. External and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
3
0
2
Order By: Relevance
“…In addition, the impact of CRPE on product greenness, demand and profit is examined, respectively. Based on existing green supply chain literature (Ma et al ., 2019a, b; Nielsen et al. , 2020) on the assignment of relevant parameters and observations of the real-world green consumer market, the parameters are assigned as follows: β = 0.8, κ = 0.5, and r = 1.…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the impact of CRPE on product greenness, demand and profit is examined, respectively. Based on existing green supply chain literature (Ma et al ., 2019a, b; Nielsen et al. , 2020) on the assignment of relevant parameters and observations of the real-world green consumer market, the parameters are assigned as follows: β = 0.8, κ = 0.5, and r = 1.…”
Section: Numerical Analysismentioning
confidence: 99%
“…The cost of green products includes two parts: production cost and total green R&D cost (Adhikari and Bisi, 2020). The unit production cost is assumed to be zero because it is negligible compared to the high total expenditure of green R&D, which is similar to Ma et al (2019b). Such assumptions can simplify calculations and better present analytic results (Zhang et al, 2021).…”
Section: Assumptions and Notationsmentioning
confidence: 99%
“…Fenomena ini sejalan dengan dengan teori Resource based view (Barney et al, 2011) yang menjelaskan hanya dengan strategic resource yang VRIO, kinerja perusahaan dan keunggulan yang berkelanjutan dapat dicapai. Secara filosofi VRIO adalah resource yang bernilai (valuable), yang langka (rareness), resource yang sulit ditiru oleh competitor (imitability), dan resource yang terorganisir (organized) dimana perusahaan harus mengantur sistem manajemen, prosesnya, kebijakan, dan budaya organisasi untuk mencapai keunggulan kompetitif yang berkelanjutan (Cardeal, 2012); (Ma et al, 2020) Dalam sudut konsumen bahwa motif aktivitas konsumen mengunjungi dan memutuskan membeli pada rumah makan tertentu bukan hanya karena lapar dan kualitas makanannya enak. Tetapi, kemungkinan disebabkan karena konsumen ingin dipersepsikan sebagai orang yang memiliki prestise tinggi, update gaya makan, ingin membuktikan referensi yang diberikan oleh seseorang, dan bahkan ingin mendapatkan pengalaman baru yang berbeda dengan sebelumnya (Elsantil & Hamza, 2021).…”
Section: Pendahuluanunclassified
“…Namun, temuan lain memilik hasil studi yang beda seperti (Piligrimiene et al, 2020), (Elsantil & Hamza, 2021) menemukan secara lansung faktor internal dan eksternal perilaku pembeli memiliki pengaruh yang lemah terhadap keputusan pembelian. Hal yang sejalan juga ditemukan oleh (Ma et al, 2020), (Popovic et al, 2019) membuktikan apabila faktor internal dan eksternal berpengaruh signifikan namun lemah terhadap keputusan pembelian.…”
Section: Pendahuluanunclassified
“…While MSMEs increase green product input, they also increase the possibility of capital constraints. The success of the green transformation of the supply chain is directly related to R&D funds, so the correct choice of financing methods has turned into the key factor to be considered in all links of the green supply chain [18]. Dash researched the impact of carbon emission reduction in green production on corporate operations and financing decisions and found that, when suppliers invest in emission reduction, a win-win situation can be achieved in terms of output and emission reduction [19].…”
Section: A Green Supply Chain Managementmentioning
confidence: 99%